2009
DOI: 10.1002/ppp.665
|View full text |Cite
|
Sign up to set email alerts
|

Two decades of responses (1986–2006) to climate by the Laurichard rock glacier, French Alps

Abstract: The Laurichard active rock glacier is the permafrost‐related landform with the longest record of monitoring in France, including an annual geodetic survey, repeated geoelectrical campaigns from 1979 onwards and continuous recording of ground temperature since 2003. These data were used to examine changes in creep rates and internal structure from 1986 to 2006. The control that climatic variables exert on rock glacier kinematics was investigated over three time scales. Between the 1980s and the early 2000s, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 95 publications
(62 citation statements)
references
References 16 publications
1
51
1
1
Order By: Relevance
“…Indeed, although no clear change of rock glaciers was detected with our methods and in our study area, several recent studies in the Alps have shown that ice-rich permafrost is more sensitive to temperature fluctuations as it becomes closer to the melting point (Kääb et al, 2007). This may lead to strong modifications of rock glacier dynamics, including a possible destabilization Roer et al, 2008;Bodin et al, 2009a). Consequently, in the Laguna Negra area, which is of critical importance for drinking water supply to the nearby city of Santiago and where glacier shrinkage subsequently increases the hydrological importance of ice-rich permafrost, recent climatic warming is likely to impact first and most strongly the dynamics and water storage capacity of rock glaciers in marginal lower elevation areas or northerly exposures.…”
Section: Geomorphological Evolution Of the Cryosphere At Its Lower LIcontrasting
confidence: 45%
“…Indeed, although no clear change of rock glaciers was detected with our methods and in our study area, several recent studies in the Alps have shown that ice-rich permafrost is more sensitive to temperature fluctuations as it becomes closer to the melting point (Kääb et al, 2007). This may lead to strong modifications of rock glacier dynamics, including a possible destabilization Roer et al, 2008;Bodin et al, 2009a). Consequently, in the Laguna Negra area, which is of critical importance for drinking water supply to the nearby city of Santiago and where glacier shrinkage subsequently increases the hydrological importance of ice-rich permafrost, recent climatic warming is likely to impact first and most strongly the dynamics and water storage capacity of rock glaciers in marginal lower elevation areas or northerly exposures.…”
Section: Geomorphological Evolution Of the Cryosphere At Its Lower LIcontrasting
confidence: 45%
“…Delaloye et al summarised annual creep rates of more than 30 rock glaciers from the European Alps, where displacements in the order of decimetres per year are reported. Bodin et al found a significant relationship between rock glacier deformation and ground temperature on the Laurichard rock glacier in the French Alps. Nevertheless, the acceleration of the creep rate of the Furggwanghorn rock glacier has slowed over the last 5 years, despite rising or almost constant ground temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned previously, 35 blocks located along three lines crossing the rock glacier (Figure 1) have been annually measured by the Parc national des Ecrins since 1999 [25]. Interannual displacements are therefore available for those points and can be compared, in the three dimensions, to the surface displacements (distance and direction) computed from images' correlation.…”
Section: Comparison Of Computed Surface Displacements With Ground-basmentioning
confidence: 99%
“…Initially, blocks were positioned using a tacheometer [21], then a total station was used from 1992-2013, and since 2012, a differential dual-frequency GPS has been used in real-time kinematic (RTK) mode. This still ongoing long-term survey has allowed quantifying the annual surface velocity of the Laurichard rock glacier along its main flow line for more than three decades [25,26] with an overall centimetric accuracy.…”
Section: Previous Studies and Monitoring Activitymentioning
confidence: 99%